Flood risk management in Austria: Analysing the shift in responsibility-sharing between public and private actors from a public stakeholder's perspective. (December 2020) - Rauter, Magdalena; Kaufmann, Maria; Thaler, Thomas; Fuchs, Sven
Highlights: Discursively, public-private responsibility sharing is increasingly debated. Institutionally, policy instruments hardly promote the use of private measures. Stabilising factors hinder institutional shift towards more responsibility sharing. Yet, factors of change are slowly emerging (e.g. expertise). Abstract: The frequency and magnitude of extreme weather events are expected to increase due to the effects of climate change and socio-economic development. Potentially higher flood risk, hence, triggered debate about a shift in flood risk management from mainly public to increasingly private involvement. So far, public flood mitigation schemes were standard modes to deal with flood hazards in many countries, including Austria. With high implementation and maintenance costs as well as substantial losses remaining, alternative management approaches have increasingly been discussed. This paper analyses the debate on shifting responsibilities in flood risk management from public to private actors and whether or not the current governance arrangement would accommodate this shift in the public-private divide. Based on qualitative research, we explicitly analyse this potential shift from an institutional perspective and not from the perspective of individual homeowners, taking the case study of Dornbirn (Austria) as an example. The results show that, firstly, the current governance arrangement hardly encourages property-level flood risk adaptation measures. Secondly, several factors stabilise the current governance arrangement and prevent a shift in the public-private divide. Although the need for an increased sense of responsibility among private actors seems to be evident among interviewees, strong historical narratives and adaptive expectations lead to a society seeing public authorities to be responsible for flood risk management and trust their expertise as well as the technical flood infrastructure. However, such areas of expertise and law are fragmented and therefore impede a redistribution or enforcement of responsibilities. Furthermore, fixed costs delay a shift in the public-private divide as the traditional engineering approach (i.e. structural measures) is predominant with high investments in the current system but limited investment in risk communication to raise awareness. Yet, a shift towards sharing responsibility might contribute to flood risk management for risks to remain manageable.